Firebug - McBride, Lish (Henry Holt and Company, 2014)
Ava, a contract killer who can start fires with her mind, hits the road with her friends, desperately trying to escape the Coterie, a magical mafia, while keeping the murder to a minimum after she's asked to kill a family friend by Venus, who killed Ava's mother.